A review of China's carbon trading market. (August 2018) - Weng, Qingqing; Xu, He
Abstract: One of the greatest constraints currently affecting China's economic development is climate change, with its associated restrictive conditions. Consequently, the application of appropriate actions to conserve energy and reduce emissions features centrally in China's core national development goals and development policies. These goals not only pose significant challenges and opportunities, but they also entail an important innovation. Under the framework of the Kyoto Protocol, the carbon trading market has emerged at a historic moment as an important measure for conserving energy and reducing emissions. Given the continuous development of the international carbon trading market over the last decade, China is also attempting to develop its own carbon trading market to further contribute to energy conservation and emissions reduction. Based on an analysis of the current situation of China's carbon trading market, relevant policy suggestions are offered here for its improvement, with the aim of providing guidelines for reducing carbon emissions, which are of mounting concern. Highlights: China has established eight carbon trading market pilots, and aims at constructing a unified national carbon trading market. The development and current status of the China's carbon trading market are combed. Several suggestions are offered for optimizing China's carbon trading market.